A tracking method of equivalent constraint boundary for offshore monopile wind turbines from measured accelerations. (15th July 2022) - Chang, Shuang; Liu, Fushun; Ji, Xiang
Abstract: For offshore wind turbines, the foundation constraint boundary is important for safe operation yet difficult to determine due to the invalidity of the fixed point assumption and influences from soil variability, liquidation, scour, etc. In this paper, a tracking method of equivalent constraint boundary is proposed on the basis of a limited numbers of measured responses, which are entirely different from the results by fixed constraints. The most theoretical achievement of the proposed method is that the time series of so-called first-order displacements can be accurately retrieved from the measured accelerations, leading to the significant difference from the first-order mode shape of conventional modal identification methods. The obvious advantage of the proposed method is that the change in the equivalent constraint boundary can be easily tracked just from the assembled accelerometers, which means that the difficulty and uncertainty of considering soil and water can be avoided. To verify the performance of the proposed method, two numerical examples and a beam experiment are conducted, and measured sea test data from a monopile wind turbine is processed. In detail, the first example is a cantilever beam with a theoretical fixed constraint position, and the results show that the fixed boundary position of the cantilever beam can be accurately estimated with a maximum relative error of 5.3% when six sensors and a fifth-order polynomial are used. The second example is a physical experiment of a cantilever beam and the change of constraint is considered by removing segments one by one. The experimental results show that the predicted constraint position is consistent with the cut length, with a maximum error of 0.009 m at 1.9 m. Furthermore, a 4 MW offshore monopile wind turbine evaluated by commercial software Ansys considering pile–soil interaction is analyzed, and the changes of the predicted equivalent constraint position are in good agreement with the preset values. Finally, the proposed method is applied to the field test data of a 6 MW monopile wind turbine, and a stable estimation of the equivalent constraint position can be obtained. The good accuracy of the proposed method demonstrates its capability in monitoring structural health for offshore wind turbines. Highlights: A tracking method of the equivalent constraint boundary for the OWT is proposed. The first-order displacement are accurately extracted from measured accelerations. Constraint changes are predicted by first-order displacements of several position. Four examples are carried out to verify and demonstrate the proposed method.